2018
DOI: 10.1007/s12035-018-0875-5
|View full text |Cite
|
Sign up to set email alerts
|

Pacific Ciguatoxin Induces Excitotoxicity and Neurodegeneration in the Motor Cortex Via Caspase 3 Activation: Implication for Irreversible Motor Deficit

Abstract: Consumption of fish containing ciguatera toxins or ciguatoxins (CTXs) causes ciguatera fish poisoning (CFP). In some patients, CFP recurrence occurs even years after exposure related to CTXs accumulation. Pacific CTX-1 (P-CTX-1) is one of the most potent natural substances known that causes predominantly neurological symptoms in patients; however, the underlying pathogenies of CFP remain unknown. Using clinically relevant neurobehavioral tests and electromyography (EMG) to assess effects of P-CTX-1 during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 104 publications
0
18
0
Order By: Relevance
“…It induced decreased body weight, reduced food consumption, and severe visceral pain after 5 h exposure was observed, mimicking the clinical gastrointestinal symptoms noted in patients with acute ciguatera poisoning, especially visceral allodynia and hyperalgesia. Neurotoxicity was also observed (Asthana et al, 2018). The toxin nomenclature used in this table and toxin synonyms are described in Section 1 of the current report.…”
Section: Acute Toxicitymentioning
confidence: 90%
“…It induced decreased body weight, reduced food consumption, and severe visceral pain after 5 h exposure was observed, mimicking the clinical gastrointestinal symptoms noted in patients with acute ciguatera poisoning, especially visceral allodynia and hyperalgesia. Neurotoxicity was also observed (Asthana et al, 2018). The toxin nomenclature used in this table and toxin synonyms are described in Section 1 of the current report.…”
Section: Acute Toxicitymentioning
confidence: 90%
“…Functional MRI studies show that there is a remarkable long-term effect of DBS on structural and functional connectivity (brain rewiring or neuroplasticity) 73 . Our electrophysiology data showed that DBS of DCN normalized aberrant neural firing leading to complete motor recovery in ataxia mice after a single and multiple SNC, whereas we performed DCN-DBS for 21 consecutive days which is the time period for active axon regeneration and function recovery 1 , 7 , 37 , 74 . Therefore, we show that an abnormal pattern of activity that is transmitted from Purkinje cells downstream to the DCN in ataxia mice can be restored for better motor recovery from PNI.…”
Section: Discussionmentioning
confidence: 88%
“…Promoting spinal plasticity by chondroitinase improve recovery of forelimb function after PNI 15 . Our work on the single and multiple SNC, that adult mice usually take 4–8 weeks to regain full motor function 1 , 7 , 37 , 74 , suggests that disruption of cerebellar circuitry leads to permanent motor deficits. This raise the intriguing possibility that the major cause of motor deficits in patients with cerebellar disorders might not be the diseases themselves but perhaps the unrecognized PNI sustained by the patients.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, another study showed a recurrent motor strength deficit associated with neuronal apoptosis, reduced spontaneous firing rate and astrogliosis in the motor cortex 4 to 6 months after intraperitoneal administration of twice the same dose. The pinprick sensory test, which assesses functions of subpopulations of A-fibers and to a lesser extent C-fibers, showed no change in mice during 4 months following P-CTX-1 exposure compared with mice exposed to P-CTX-1 vehicle [ 211 ].…”
Section: Pathophysiological Basis Of Ciguatera Neurological Disturmentioning
confidence: 99%